RANDOM CONTRACTION SCHEMES FOR EXTREMAL ORDER STATISTICS - Saghatelyan, V.K. (Proceedings of the YSU A: Physical and Mathematical Sciences, 2012)
In this paper a few new types of random contraction and dilation schemes are considered. In particular, four one-sided additive schemes and two two-sided additive schemes are represented. All schemes has been built for sample extremes and exponential random variables. Characterizations of distributions for all those schemes are obtained.